Low-Protein Diet Supplemented with Amino Acids Can Regulate the Growth Performance, Meat Quality, and Flavor of the Bamei Pigs - Dong Wang; Ke Hou; Mengjie Kong; Wei Zhang; Wenzhong Li; Yiwen Geng; Chao Ma; Guoshun Chen (Foods)
This study evaluated the impact of reduced crude protein (CP) diets supplemented with four essential amino acids (EAAs) on production efficiency and meat quality characteristics in Bamei pigs. Thirty-six castrated Bamei pigs (half male and half female, 100 days old, with an average body weight of 50.65 kg) were randomly assigned to three different dietary CP levels: control group (16.0% CP), group I (14.0% CP + EAA), and group II (12.0% CP + EAA). In both experiments, the group I and group II diets were supplemented with crystalline AA to achieve equal contents of standardized ileal digestible (SID) lysine, methionine, threonine, and tryptophan. After a 70-day feeding trial, the results showed that (1) low-protein diets of different levels supplemented with four EAAs had no significant effect on the growth performance of Bamei pigs (p > 0.05) but had a tendency to increase average daily feed intake (ADFI). (2) In terms of slaughter performance, compared with the control group, the low-protein amino-acid-balanced diet significantly reduced the pH of gastric contents (p = 0.045), and tended to increase the backfat thickness and dressing percentage (p > 0.05). (3) The effect of low-protein diets on muscle amino acids showed that group I was significantly improved, including increased Threonine, Serine, Glycine and Bitter amino acids. (4) Compared with the control group, the low-protein group increased the ratio of unsaturated fatty acid (UFA)/total fatty acids (TFAs), Monounsaturated Fatty Acid (MUFA)/TFA, and Polyunsaturated Fatty Acid (PUFA)/TFA, and the content of decanoic acid, myristic acid, and cis-11-eicosenoic acid in group II was significantly higher than that in the other two groups (p ≤ 0.012). (5) The total number of flavor compounds in the muscle of the low-protein group was higher than that of the control group, including Aldehyde, Alcohol, sulfide, Alkane, and Furan compounds. Among them, the relative contents of Hexanal, Heptaldehyde, Benzaldehyde, E-2-Octenal, 2,3-Octanedione, and 2-Pentylfuran in group II were significantly higher than in those groups (p < 0.05). Notably, the 14% dietary protein level group had the most significant effect on the meat quality and flavor of Bamei pigs. Therefore, under the condition of amino acid balance, reducing the use of protein feed raw materials and adding synthetic amino acids can not only improve the meat quality and flavor of finishing pigs, but also save the feed cost.